Evaluation of the mean Venous Hounsfield Value in Non-Contrast CT scans of the Brains of Patients with Cerebral Venous Thrombosis Compared to Normal People - Zia Kashani, Seyed Ali; Bazmandegan, Gholamreza; Zare Ranjbar, Hamed; Kamiab, Zahra; Mohammadi, Shima; Ahmadpour, Negin (Novelty in Biomedicine, 2025)
Background: Cerebral Venous Sinus Thrombosis (CVST) is a significant cause of stroke associated with elevated morbidity and mortality rates, presenting diagnostic challenges. Non-contrast computed tomography (NCCT) is among the initial imaging modalities utilized for patients presenting with neurological symptoms or those who have experienced trauma. Research indicates a potential association between venous Hounsfield (HU) values in brain NCCT and CVST; however, the existing studies in this regard remain limited. This study investigates the relationship between the venous HU value from NCCT of the brain and CVST. Materials and Methods: This retrospective case-control study was conducted on patients referred to Ali Ibn Abi Taleb Hospital (Rafsanjan, Iran) from the start to the end of 2024. Patients with CVST who were admitted to the neurological emergency department with suspected clinical symptoms were studied as the case group (30 patients), and normal individuals (30 people) were studied as the control group. Patient information, including age, sex, involved vein, and final opinion of radiologists regarding venous involvement, was recorded. The significance level was considered less than 0.05. Results: NCCT images were compared between the groups. There was no statistically significant difference between the two groups in terms of age, sex, and smoking (P-values > 0.05). The most common site of thrombosis was the superior sagittal sinus (53.3%). The mean attenuation in the CVST group was 63.67 ± 1.9 HU, and in the control group it was 52.03 ± 1.25 HU (P-value < 0.01). Hemoglobin levels were within normal limits in both groups. Still, they were significantly lower in the CVST group (P-value: 0.014), and with a one-unit increase in hemoglobin level, the probability of CVST increased by about 33.2% (95% CI: 1.050–1.690). Frequency of OCP use, previous history of abortion, and previous history of thrombosis did not differ statistically significantly between the groups (all P-values > 0.05). Conclusion: Higher attenuation in the NCCT of these patients may be used as a diagnostic criterion in the clinic.